Modified lithium-sulfur battery diaphragm, preparation method thereof and lithium-sulfur battery
By depositing metal oxide nanolayers on the lithium-sulfur battery separator and building a functional interlayer, the problem of low battery performance caused by the polysulfide shuttle effect is solved, and the battery performance and safety improvement are achieved.
Patent Information
- Application Number
- CN202411952002.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-25
AI Technical Summary
The existing lithium-sulfur battery separators have low battery performance due to the shuttle effect of polysulfides, which affects capacity, energy density and service life.
Metal oxide nanolayers are uniformly deposited on the substrate of the lithium-sulfur battery separator, and amorphous metal oxide nanolayers are prepared by physical vapor deposition method, and a functional interlayer is constructed to suppress the shuttle effect of polysulfides.
It significantly improves the cycle life and Coulomb efficiency of lithium-sulfur batteries, reduces capacity attenuation, and improves the safety performance of the battery.
Smart Images

Figure CN119695391A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of energy storage materials and lithium-sulfur battery diaphragms, and in particular to a modified lithium-sulfur battery diaphragm and a preparation method thereof, and a lithium-sulfur battery. Background Art
[0002] With the rapid development of social economy, the demand for new energy electric vehicles, portable electronic devices and other electronic devices is increasing, resulting in a large amount of energy consumption. Traditional energy supply methods can no longer meet this rapidly growing demand, so the development of new high energy density battery technology has become particularly important.
[0003] At present, lithium-ion batteries with graphite as negative electrodes dominate the market, but their performance improvement has gradually reached the theoretical limit. Specifically, the theoretical capacity of lithium-ion batteries is very close to its upper limit and it is difficult to increase it significantly. In addition, lithium-ion batteries still have some inherent problems, such as safety hazards, high costs and relatively low theoretical energy density, which limit the further application of lithium-ion batteries in portable electronic devices and electric vehicles.
[0004] As an emerging high-energy-density battery technology, lithium-sulfur batteries have shown great potential and are expected to replace or partially replace lithium-ion batteries in the future and become the mainstream energy supply method in the fields of new energy electric vehicles, portable electronic devices, etc. Lithium-sulfur batteries use sulfur as the positive electrode material and metallic lithium as the negative electrode to store and release energy through the electrochemical reaction between sulfur and lithium. Compared with lithium-ion batteries, lithium-sulfur batteries have better theoretical specific capacity and energy density. This means that at the same weight or volume, lithium-sulfur batteries can store more energy and provide longer service time. At the same time, the positive electrode material of lithium-sulfur batteries, sulfur, is abundant in the earth's crust, so the price is relatively low. Sulfur is also less toxic and has less impact on the environment and human health. These factors make lithium-sulfur batteries have great advantages in terms of cost and environmental friendliness.
[0005] Although lithium-sulfur batteries have many advantages, their commercialization process still faces some technical challenges. For example, the shuttle effect of polysulfides and battery safety issues need further research and resolution. The shuttle effect of polysulfides not only directly affects the capacity and energy density of the battery, but also affects the storage performance of the battery and shortens the battery life. Summary of the invention
[0006] In order to solve the problem of low battery performance caused by the shuttle effect of polysulfides in the existing lithium-sulfur battery separator, the purpose of the present invention is to provide a modified lithium-sulfur battery separator and a preparation method thereof and a lithium-sulfur battery, which can inhibit the shuttle effect of polysulfides and improve the battery performance of the lithium-sulfur battery without changing the porous structure of the separator.
[0007] To achieve the above objectives, the technical solution of the present invention is as follows.
[0008] The first aspect of the present invention provides a modified lithium-sulfur battery separator, which comprises a separator substrate and a metal oxide nanolayer, wherein the metal oxide nanolayer is uniformly deposited on the surface of the separator substrate by a physical vapor deposition method; the metal oxide is at least one of titanium dioxide, indium oxide, aluminum oxide, beryllium oxide, magnesium oxide, calcium oxide, barium oxide, zirconium dioxide, vanadium oxide, niobium oxide, chromium oxide, manganese oxide, technetium dioxide, rhenium heptoxide, silver oxide, zinc oxide, cadmium oxide, germanium dioxide, tin oxide, antimony trioxide, and bismuth oxide; and the thickness of the metal oxide nanolayer is 10 nm to 50 nm.
[0009] In the present invention, the chemical formula of titanium dioxide is TiO2; the chemical formula of indium oxide is In2O3; the chemical formula of aluminum oxide is Al2O3; the chemical formula of beryllium oxide is BeO; the chemical formula of magnesium oxide is MgO; the chemical formula of calcium oxide is CaO; the chemical formula of barium oxide is BaO; the chemical formula of zirconium dioxide is ZrO2; the chemical formula of vanadium oxide is V2O5; the chemical formula of niobium oxide is Nb2O5; the chemical formula of chromium oxide is Cr2O3; the chemical formula of manganese oxide is MnO; the chemical formula of technetium dioxide is TcO2; the chemical formula of rhenium heptoxide is Re2O7; the chemical formula of silver oxide is Ag2O; the chemical formula of zinc oxide is ZnO; the chemical formula of cadmium oxide is CdO; the chemical formula of germanium dioxide is GeO2; the chemical formula of tin oxide is SnO2; the chemical formula of antimony trioxide is Sb2O3; and the chemical formula of bismuth oxide is Bi2O3.
[0010] The modified lithium-sulfur battery separator of the present invention comprises a separator substrate and a metal oxide nanolayer, and the nano-scale metal oxide is uniformly attached to the separator substrate by a magnetron sputtering method to modify the separator substrate. The metal oxide nanolayer is used to form a functional interlayer between the positive electrode and the separator to inhibit the shuttle effect of the positive electrode, thereby solving the problem of low battery performance caused by the shuttle effect of polysulfide in the existing lithium-sulfur battery separator.
[0011] Preferably, the metal oxide is at least one of titanium dioxide, indium oxide, and aluminum oxide. In the present invention, the lithium-sulfur battery separator modified with titanium dioxide, indium oxide, and aluminum oxide can achieve a first-cycle charge and discharge coulomb efficiency of more than 90% within a sputtering time of 4 to 20 minutes, and after 150 cycles, the discharge voltage is still maintained at a high level, while maintaining a high capacity retention rate of more than 50%.
[0012] Preferably, the diaphragm substrate is any one of a polyethylene diaphragm, a polypropylene microporous diaphragm, and a cellulose diaphragm.
[0013] Preferably, the thickness of the metal oxide nanolayer is 10 to 50 nm.
[0014] The second aspect of the present invention provides a method for preparing the modified lithium-sulfur battery separator according to the first aspect, comprising the following steps:
[0015] A metal oxide nanolayer is uniformly deposited on the surface of a diaphragm substrate by a physical vapor deposition method to obtain a lithium-sulfur battery diaphragm modified with a metal oxide nanolayer.
[0016] Preferably, the target material for depositing the metal oxide nanolayer is a corresponding metal oxide target material. The corresponding metal oxide target materials are targets corresponding to at least one metal oxide selected from titanium dioxide, indium oxide, aluminum oxide, beryllium oxide, magnesium oxide, calcium oxide, barium oxide, zirconium dioxide, vanadium oxide, niobium oxide, chromium oxide, manganese oxide, technetium dioxide, rhenium heptoxide, silver oxide, zinc oxide, cadmium oxide, germanium dioxide, tin oxide, antimony trioxide, and bismuth oxide.
[0017] Preferably, the process parameters for depositing the metal oxide nanolayer are: the background vacuum is 0.1×10 -5 Pa~9.9×10 -5 Pa, working gas pressure is 0.25Pa~0.35Pa, purity of metal oxide target is ≥99.99%; target distance is 8cm~12cm, sputtering temperature is 20℃~30℃, sputtering time is 1min~20min. According to different target materials, select the optimal process parameters such as sputtering time, sputtering power and sputtering gas pressure.
[0018] The present invention is based on the existing diaphragm substrate and adopts radio frequency magnetron sputtering process to sputter nanometer-scale metal oxide nanolayer on the surface of the diaphragm substrate, and controls the deposition of lithium in space by strictly controlling the process parameters of the sputtering process; at the same time, according to different oxides, different sputtering process parameters such as sputtering time, sputtering power, sputtering gas pressure are selected, so that the thickness of the deposited metal oxide nanolayer can ensure the performance of the diaphragm itself in transmitting lithium ions while maintaining the physical shielding effect on soluble polysulfides.
[0019] The third aspect of the present invention provides a lithium-sulfur battery, which consists of a positive electrode, a separator, a negative electrode and an electrolyte solution; the separator is the modified lithium-sulfur battery separator described in the first aspect; the lithium-sulfur battery consists of a positive electrode, a separator, a negative electrode and an electrolyte solution; the positive electrode is obtained by grinding a sulfur-carbon composite material with Super-P carbon and polyvinylidene fluoride, dispersing the mixture in N-methylpyrrolidone, ball milling to obtain a positive electrode slurry, and coating the mixture on a metal substrate; the negative electrode is polished lithium metal; the electrolyte solution is obtained by mixing 1,3-dioxolane and 1,2-dimethoxyethane in an equal volume ratio, adding a lithium nitrate solution and lithium bis(trifluoromethanesulfonyl)imide, and mixing them evenly.
[0020] The present invention constructs a functional interlayer between the positive electrode and the diaphragm by attaching a metal oxide nanolayer on the side of the diaphragm substrate facing the positive electrode to suppress the shuttle effect of the positive electrode. After the modified lithium-sulfur battery diaphragm of the present invention is used to assemble a lithium-sulfur battery, it can improve the cycle life and coulomb efficiency of the lithium-sulfur battery, and also prevent it from producing irreversible capacity decay. Specifically, as the number of cycles increases, the capacity of the battery remains stable, and after 150 cycles, the discharge capacity remains at a high level. Moreover, due to the optimization treatment of the surface of one side of the diaphragm by the bifunctional metal oxide nanolayer, the possibility of soluble polysulfide passing through the diaphragm is significantly reduced during the use of the lithium-sulfur battery, thereby avoiding the loss of active sulfur. At the same time, this optimization treatment ensures the uniformity of the lithium ion flux, effectively prevents lithium dendrites from penetrating the SEI film, and avoids the internal short circuit and safety problems of the battery that may be caused by contact with the positive electrode after it gradually grows. Therefore, the lithium-sulfur battery using this special diaphragm not only significantly improves the safety performance in use, but also extends the cycle life of the battery and improves its coulomb efficiency.
[0021] The full name of SEI in English is Solid Electrolyte Interface. The Chinese name of SEI membrane is solid electrolyte interface membrane. SEI membrane is a passivation layer covering the surface of electrode material formed by the reaction between electrode material and electrolyte solution at the solid-liquid interface during the first charge and discharge process of lithium-ion battery. This passivation layer is an interface layer with the characteristics of solid electrolyte. It is an electronic insulator and an excellent conductor of lithium ions. Lithium ions can be freely embedded and extracted through this passivation layer.
[0022] Preferably, in the positive electrode, the sulfur-carbon composite material is obtained by heating sulfur and acetylene black at 140° C. to 150° C.; the mass ratio of sulfur to acetylene black is 7:3; and the metal substrate is aluminum foil or copper foil.
[0023] Preferably, the mass ratio of the sulfur-carbon composite material to the Super-P carbon and polyvinylidene fluoride is 8:1:1.
[0024] Preferably, in the electrolyte solution, the mass fraction of lithium nitrate solution is 1.0%; and the concentration of lithium bis(trifluoromethanesulfonyl)imide in the electrolyte solution is 1 mol / L.
[0025] Preferably, in the preparation process of the positive electrode, the ball milling time is 1 h to 2 h; after coating on the metal substrate, vacuum drying is also included, the vacuum drying temperature is 50° C. to 60° C., and the vacuum drying time is 8 h to 12 h.
[0026] Preferably, the polishing of the negative electrode, the preparation of the electrolyte solution and the assembly of the lithium-sulfur battery are all carried out in a glove box with an argon protective atmosphere, wherein the contents of oxygen and water in the argon protective atmosphere are less than 0.1 ppm.
[0027] Beneficial effects of the present invention:
[0028] 1. The present invention attaches a metal oxide nanolayer on one side surface of the diaphragm substrate by a physical vapor deposition method. The additional metal oxide nanolayer is constructed to form a functional interlayer between the positive electrode and the diaphragm, which acts as a physical shield. On the basis of allowing lithium ions to pass, it inhibits the shuttle effect of soluble polysulfides. At the same time, the amorphous metal oxide nanolayer prepared by the physical vapor deposition method of the present invention has good structural uniformity and porosity, increases the contact area between the electrolyte and the functional interlayer, makes the diaphragm surface have better wettability for the electrolyte, and enables lithium to be uniformly deposited on the negative electrode side, thereby realizing the uniform deposition process of lithium in space. Under the action of such a dual-functional coating, not only the shuttle effect of soluble polysulfides is solved, but also the rapid conduction of lithium ions is facilitated, and the dendrite-free growth of lithium is promoted. This significantly improves the Coulomb efficiency and cycle life of lithium-sulfur batteries and reduces the attenuation of their capacity.
[0029] 2. The modified lithium-sulfur battery separator of the present invention is used to prepare lithium-sulfur batteries, which can significantly improve the charge and discharge cycle performance of lithium-sulfur batteries. Specifically, as the number of cycles increases, the capacity of the battery remains stable, and after 150 cycles, the discharge capacity still remains at a high level; and the battery's safety performance is improved, and its cycle life and coulombic efficiency are improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1This is a test diagram of the electrochemical performance of a lithium-sulfur full battery using the modified lithium-sulfur battery separator modified with titanium dioxide with different sputtering times in Example 1. Among them, (A) is a curve diagram showing the discharge capacity of the lithium-sulfur full battery using the comparative example 1 and the lithium-sulfur full battery using the modified lithium-sulfur battery separator modified with titanium dioxide with different sputtering times in Example 1 as a function of the number of cycles; (B) is a curve diagram showing the voltage of the lithium-sulfur full battery using the comparative example 1 after 150 cycles as a function of the specific capacity; (C) is a curve diagram showing the voltage of the lithium-sulfur full battery using the modified lithium-sulfur battery separator modified with titanium dioxide with a sputtering time of 4 min in Example 1 after 150 cycles as a function of the specific capacity; (D) is a curve diagram showing the voltage of the lithium-sulfur full battery using the modified lithium-sulfur battery separator modified with titanium dioxide with a sputtering time of 8 min in Example 1 after 150 cycles as a function of the specific capacity; (E) is a curve diagram showing the voltage of the lithium-sulfur full battery using the modified lithium-sulfur battery separator modified with titanium dioxide with a sputtering time of 20 min in Example 1 after 150 cycles as a function of the specific capacity.
[0031] Figure 2 This is a test diagram of the electrochemical performance of a lithium-sulfur full battery using the modified lithium-sulfur battery separator modified with indium oxide with different sputtering times in Example 2. Among them, (A) is a curve diagram showing the discharge capacity of the lithium-sulfur full battery using the comparative example 1 and the lithium-sulfur full battery using the modified lithium-sulfur battery separator modified with indium oxide with different sputtering times in Example 2 as a function of the number of cycles; (B) is a curve diagram showing the voltage of the lithium-sulfur full battery using the comparative example 1 after 150 cycles as a function of the specific capacity; (C) is a curve diagram showing the voltage of the lithium-sulfur full battery using the modified lithium-sulfur battery separator modified with indium oxide with a sputtering time of 4 min in Example 2 after 150 cycles as a function of the specific capacity; (D) is a curve diagram showing the voltage of the lithium-sulfur full battery using the modified lithium-sulfur battery separator modified with indium oxide with a sputtering time of 8 min in Example 2 after 150 cycles as a function of the specific capacity; (E) is a curve diagram showing the voltage of the lithium-sulfur full battery using the modified lithium-sulfur battery separator modified with indium oxide with a sputtering time of 20 min in Example 2 after 150 cycles as a function of the specific capacity.
[0032] Figure 3The electrochemical performance test diagram of the lithium-sulfur full battery using the modified lithium-sulfur battery separator modified by aluminum oxide with different sputtering times in Example 3. Among them, (A) is a curve diagram showing the discharge capacity of the lithium-sulfur full battery using the comparative example 1 and the lithium-sulfur full battery using the modified lithium-sulfur battery separator modified by aluminum oxide with different sputtering times in Example 3 as a function of the number of cycles; (B) is a curve diagram showing the voltage of the lithium-sulfur full battery using the comparative example 1 after 150 cycles as a function of the specific capacity; (C) is a curve diagram showing the voltage of the lithium-sulfur full battery using the modified lithium-sulfur battery separator modified by aluminum oxide with a sputtering time of 4 min in Example 3 as a function of the specific capacity after 150 cycles; (D) is a curve diagram showing the voltage of the lithium-sulfur full battery using the modified lithium-sulfur battery separator modified by aluminum oxide with a sputtering time of 16 min in Example 3 as a function of the specific capacity after 150 cycles. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0034] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.
[0035] During the operation of lithium-sulfur batteries, the inherent insulating properties of sulfur and insoluble Li2S lead to poor electrochemical kinetics, low utilization of active sulfur and low Coulombic efficiency of lithium-sulfur batteries. In addition, the sulfur cathode is gradually reduced during discharge to produce a series of soluble long-chain polysulfide intermediates. These polysulfides have high solubility and can be dissolved in organic electrolyte solutions. Due to the presence of concentration gradients, these dissolved polysulfides diffuse from the positive electrode region through the electrolyte solution to the negative electrode region. This is the shuttle effect or shuttle effect of the sulfur cathode of the lithium-sulfur battery.
[0036] The existence of the shuttle effect has brought many technical problems to lithium-sulfur batteries. First, the irreversible reaction of polysulfides on the surface of the negative electrode will lead to the loss of active substances, which will directly affect the capacity and energy density of the battery, resulting in poor cycle performance. Secondly, polysulfides dissolved in the electrolyte are prone to internal short circuits between the positive and negative electrodes, leading to self-discharge of the battery, which not only affects the storage performance of the battery, but also shortens the service life of the battery. In addition, the shuttle effect will also lead to a decrease in the charging and discharging efficiency of the battery, that is, a decrease in the Coulomb efficiency, which further weakens the overall performance of the battery. Moreover, the shuttle effect will corrode the lithium anode, aggravate the growth and uneven deposition of lithium dendrites, and seriously affect the rate performance and safety of lithium-sulfur batteries.
[0037] At present, most strategies to improve the performance of lithium-sulfur batteries focus on the design of electrode materials, for example, solving the insulation problem of sulfur by doping sulfur in highly conductive graphene and carbon nanotube frameworks. Similar designs all enhance the electrochemical performance of lithium-sulfur batteries through morphology control and structural engineering, but the relative content of encapsulated sulfur in the positive electrode is low, which greatly offsets the advantages of lithium-sulfur batteries in high energy density. At the same time, such designs still use commercial polyolefin separators, such as polypropylene separators and polyethylene separators. Such separators have low porosity, poor electrolyte affinity, and poor thermal stability. In addition, the shuttle effect leads to loss of active sulfur substances and rapid capacity decay. Problems such as these remain to be solved, and common separator modification methods containing a large amount of adhesives will block the membrane pores, resulting in low ionic conductivity and causing obvious difficulties in application.
[0038] The existing technology for modifying lithium-sulfur battery separators mainly uses metal oxide nanoparticles mixed with polymer materials and then coated on the separator. However, since the separator is a porous material and has the function of conducting ions, the pores on the porous separator are easily blocked by the above-mentioned coating method, affecting the transmission of ions.
[0039] The present invention uses the technology of physical vapor deposition to introduce an oxide nanolayer on the surface of the diaphragm facing the positive electrode. The oxide nanolayer acts as a physical shield to allow lithium ions to pass through, while suppressing the shuttle effect of soluble polysulfides. At the same time, the amorphous metal oxide nano-scale coating prepared by magnetron sputtering technology has good structural uniformity and porosity. On the basis of ensuring the porous structure of the diaphragm, the bonding force between the oxide nanolayer and the diaphragm substrate is improved. The metal oxide nanolayer introduced by the present invention captures or converts polysulfides by electrostatic adsorption or catalysis, thereby preventing them from diffusing from the positive electrode to the negative electrode. The modified lithium-sulfur battery diaphragm of the present invention retains the porous structure of the diaphragm substrate, does not change its original pore structure, and the oxide nanolayer is very uniform. In addition, the diaphragm with an oxide nanolayer introduced by the present invention increases the contact area between the electrolyte and the interlayer, so that the diaphragm surface has better wettability to the electrolyte, so that lithium can be uniformly deposited on the negative electrode side, thereby realizing the spatial control of the uniform deposition process of lithium. Under the action of such a dual-functional coating, it not only solves the shuttle effect of soluble polysulfides, but also facilitates the rapid conduction of lithium ions and promotes dendrite-free growth of lithium.
[0040] The technical scheme of the present invention is further described below by means of specific examples. The methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are all commercially available unless otherwise specified.
[0041] In the following embodiments, the lithium-sulfur battery separator purchased in advance as the separator substrate is any one of a polyethylene separator, a polypropylene microporous separator, and a cellulose separator; the separator substrate is a commercially available separator of Celgard. The polyethylene separator is taken as an example to explain the technical solution of the present invention in detail. In the following embodiments, super-P is a small particle conductive carbon black, which is a pure black ultra-fine powder, used as a conductive agent to play a conductive role.
[0042] Example 1
[0043] A method for preparing a titanium dioxide-modified modified lithium-sulfur battery separator comprises the following steps:
[0044] The titanium dioxide nanolayer is uniformly deposited on the lithium-sulfur battery separator substrate through the radio frequency magnetron sputtering process. Specifically:
[0045] The pre-purchased lithium-sulfur battery diaphragm is installed as the diaphragm base on the sample tray in the sputtering chamber and covered with a baffle. The pre-purchased lithium-sulfur battery diaphragm is a polyethylene diaphragm. The titanium dioxide target with a purity of 99.99% is cleaned and dried with acetone, and then pre-sputtered for 5 minutes to remove surface oxides and other impurities to ensure that pure titanium dioxide is deposited on the surface of the subsequent diaphragm. Depending on the target material, we need to choose the preferred sputtering time, sputtering power and sputtering gas pressure. Open the baffle of the sample tray and start sputtering titanium dioxide. The process parameters of DC magnetron sputtering are: at a background vacuum of 5.0×10 -4 When the argon gas with a purity of 99.99% is introduced at 0.30Pa, the working pressure is 0.30Pa, the target distance is 10cm, the sputtering power is 70W, the sputtering temperature is 25℃, and the sputtering is performed for 1min to 20min. After the sputtering is completed, a modified lithium-sulfur battery separator with a nano-scale titanium dioxide coating on the surface is obtained.
[0046] According to the above method, modified lithium-sulfur battery separators with nano-scale titanium dioxide coating on the surface were prepared at different sputtering times of 4 minutes, 8 minutes and 20 minutes respectively.
[0047] Example 2
[0048] A method for preparing a modified lithium-sulfur battery separator modified with indium oxide, comprising the following steps:
[0049] The indium oxide nanolayer is uniformly deposited on the lithium-sulfur battery separator substrate through a radio frequency magnetron sputtering process. Specifically:
[0050] The pre-purchased lithium-sulfur battery diaphragm is installed as the diaphragm base on the sample tray in the sputtering chamber and covered with a baffle. The pre-purchased lithium-sulfur battery diaphragm is a polyethylene diaphragm. After the indium oxide target with a purity of 99.99% is cleaned and dried with acetone, it is pre-sputtered for 5 minutes to remove surface oxides and other impurities to ensure that pure indium oxide is deposited on the surface of the subsequent diaphragm. Depending on the target material, we need to choose the preferred sputtering time, sputtering power and sputtering gas pressure. Open the baffle of the sample tray and start sputtering indium oxide. The process parameters of DC magnetron sputtering are: at the background vacuum degree of 0.1×10 -4 When the argon gas with a purity of 99.99% is introduced at 1.5 Pa, the working pressure is 0.25 Pa, the target distance is 8 cm, the sputtering power is 75 W, the sputtering temperature is 25° C., and the sputtering is performed for 1 to 20 minutes. After the sputtering is completed, a modified lithium-sulfur battery separator with a nano-scale indium oxide coating on the surface is obtained.
[0051] According to the above method, modified lithium-sulfur battery separators with nano-scale indium oxide coatings on the surface were prepared at different sputtering times of 4 min, 8 min and 20 min respectively.
[0052] Example 3
[0053] A method for preparing an aluminum oxide modified lithium-sulfur battery separator comprises the following steps:
[0054] The aluminum oxide nanolayer is uniformly deposited on the lithium-sulfur battery separator substrate through a radio frequency magnetron sputtering process. Specifically:
[0055] The pre-purchased lithium-sulfur battery diaphragm is installed as the diaphragm base on the sample tray in the sputtering chamber and covered with a baffle. The pre-purchased lithium-sulfur battery diaphragm is a polyethylene diaphragm. After the 99.99% pure alumina target is cleaned and dried with acetone, it is pre-sputtered for 5 minutes to remove surface oxides and other impurities to ensure that pure alumina is deposited on the subsequent diaphragm surface. Depending on the target material, we need to choose the preferred sputtering time, sputtering power and sputtering gas pressure. Open the baffle of the sample tray and start sputtering alumina. The process parameters of DC magnetron sputtering are: at the background vacuum degree of 0.1×10 -4 When the argon gas with a purity of 99.99% is introduced at 1.5 Pa, the working pressure is 0.25 Pa, the target distance is 8 cm, the sputtering power is 75 W, the sputtering temperature is 25 ° C, and the sputtering is 1 min to 16 min. After the sputtering is completed, a modified lithium-sulfur battery separator with a nano-scale aluminum oxide coating on the surface is obtained.
[0056] According to the above method, modified lithium-sulfur battery separators with nano-scale aluminum oxide coatings on the surface were prepared at different sputtering times of 4 minutes and 16 minutes respectively.
[0057] Example 4
[0058] Modified lithium-sulfur battery separators modified with other metal oxides were prepared according to the method of Example 1, as shown in Table 1. The sputtering time was 8 min.
[0059] Table 1 Raw material feeding of metal oxide modified lithium sulfur battery separator
[0060] serial number Metal oxides 4a-1 Beryllium Oxide 4a-2 Magnesium Oxide 4a-3 Calcium Oxide 4a-4 Barium Oxide 4a-5 Zirconium Dioxide 4a-6 Vanadium Oxide 4a-7 Niobium oxide 4a-8 Chromium oxide 4a-9 Manganese oxide 4a-10 Titanium dioxide and indium oxide are mixed in a mass ratio of 1:1 4a-11 Titanium dioxide and aluminum oxide are in a mass ratio of 1:1 4a-12 Titanium dioxide and magnesium oxide in a mass ratio of 1:1
[0061] Comparative Example 1
[0062] A lithium-sulfur battery separator adopts a pre-purchased lithium-sulfur battery separator, and the pre-purchased lithium-sulfur battery separator is a polyethylene separator.
[0063] Application Example 1
[0064] The modified lithium-sulfur battery separator prepared in Example 1 is used to assemble a lithium-sulfur full battery, and the specific method is as follows:
[0065] Sulfur and acetylene black were mixed in a weight ratio of 7:3 and heated at 150°C to prepare a sulfur-carbon composite material. The prepared sulfur-carbon composite material was then ground and mixed with Super-P carbon and polyvinylidene fluoride in a weight ratio of 8:1:1, and dispersed in N-methylpyrrolidone to form a mixture. The mixture was ball-milled to obtain a positive electrode slurry; the positive electrode slurry was dripped onto aluminum foil, and the slurry was evenly spread on the aluminum foil with a scraper, and the positive electrode of the lithium-sulfur battery was obtained after vacuum drying.
[0066] Lithium bis(trifluoromethanesulfonyl imide), referred to as LiTFSI. 1,3-dioxolane and 1,2-dimethoxyethane were mixed in equal volumes, and 1.0% by mass of lithium nitrate was added to obtain a mixed solution A; lithium bis(trifluoromethanesulfonyl imide) was dispersed in the mixed solution A, and the concentration of lithium bis(trifluoromethanesulfonyl imide was 1 mol / L to obtain an electrolyte solution.
[0067] After the lithium metal is polished, it is used as the negative electrode of the battery. The polished lithium metal negative electrode, the modified lithium-sulfur battery separator of Example 1, and the positive electrode are placed in a standard CR2032 button battery shell containing 30 μL of electrolyte solution, wherein the plated side of the modified lithium-sulfur battery separator faces the positive electrode; the polishing of the negative electrode, the preparation of the electrolyte solution, and the assembly of the battery are all carried out in an argon-protected glove box; a lithium-sulfur battery with a nano-scale titanium dioxide coating on the separator is prepared.
[0068] Application Example 2
[0069] The modified lithium-sulfur battery separator prepared in Example 2 is used to assemble a lithium-sulfur full battery, and the specific method is as follows:
[0070] Sulfur and acetylene black were mixed in a weight ratio of 7:3 and heated at 150°C to prepare a sulfur-carbon composite material. The prepared sulfur-carbon composite material was then ground and mixed with Super-P carbon and polyvinylidene fluoride in a weight ratio of 8:1:1, and dispersed in N-methylpyrrolidone to form a mixture. The mixture was ball-milled to obtain a positive electrode slurry; the positive electrode slurry was dripped onto aluminum foil, and the slurry was evenly spread on the aluminum foil with a scraper, and the positive electrode of the lithium-sulfur battery was obtained after vacuum drying.
[0071] 1,3-dioxolane and 1,2-dimethoxyethane were mixed in equal volumes, and 1.0 mass% lithium nitrate was added to prepare a mixed solution A; lithium bis(trifluoromethanesulfonyl)imide was dispersed in the mixed solution A, and the concentration of lithium bis(trifluoromethanesulfonyl)imide was 1 mol / L, to prepare an electrolyte solution.
[0072] After the lithium metal is polished, it is used as the negative electrode of the battery. The polished lithium metal negative electrode, the modified lithium-sulfur battery separator of Example 2, and the positive electrode are placed in a standard CR2032 button battery shell containing 30 μL of electrolyte solution, wherein the plated side of the modified lithium-sulfur battery separator faces the positive electrode; the polishing of the negative electrode, the preparation of the electrolyte solution, and the assembly of the battery are all carried out in an argon-protected glove box; a lithium-sulfur battery with a nano-scale indium oxide coating on the separator is prepared.
[0073] Application Example 3
[0074] The modified lithium-sulfur battery separator prepared in Example 3 is used to assemble a lithium-sulfur full battery, and the specific method is as follows:
[0075] Sulfur and acetylene black were mixed in a weight ratio of 7:3 and heated at 150°C to prepare a sulfur-carbon composite material. The prepared sulfur-carbon composite material was then ground and mixed with Super-P carbon and polyvinylidene fluoride in a weight ratio of 8:1:1, and dispersed in N-methylpyrrolidone to form a mixture. The mixture was ball-milled to obtain a positive electrode slurry; the positive electrode slurry was dripped onto aluminum foil, and the slurry was evenly spread on the aluminum foil with a scraper, and the positive electrode of the lithium-sulfur battery was obtained after vacuum drying.
[0076] 1,3-dioxolane and 1,2-dimethoxyethane were mixed in equal volumes, and 1.0 mass% lithium nitrate was added to prepare a mixed solution A; lithium bis(trifluoromethanesulfonyl)imide was dispersed in the mixed solution A, and the concentration of lithium bis(trifluoromethanesulfonyl)imide was 1 mol / L, to prepare an electrolyte solution.
[0077] After the lithium metal is polished, it is used as the negative electrode of the battery. The polished lithium metal negative electrode, the modified lithium-sulfur battery separator of Example 3, and the positive electrode are placed in a standard CR2032 button battery shell containing 30 μL of electrolyte solution, wherein the plated side of the modified lithium-sulfur battery separator faces the positive electrode; the polishing of the negative electrode, the preparation of the electrolyte solution, and the assembly of the battery are all carried out in an argon-protected glove box; a lithium-sulfur battery with a nano-scale aluminum oxide coating on the separator is prepared.
[0078] Application Example 4
[0079] According to the method of Application Example 1, the modified lithium-sulfur battery separator modified with other metal oxides prepared in Example 4 is used to assemble a lithium-sulfur full battery.
[0080] Application Comparative Example 1
[0081] The lithium-sulfur battery separator of Comparative Example 1 was used to assemble a lithium-sulfur full battery according to the method of Application Example 1.
[0082] Test Example 1:
[0083] The lithium-sulfur batteries prepared in Example 1 and Comparative Example 1 were subjected to charge and discharge comparison tests. The charge and discharge current of the test was set to 0.5 mA / cm 2 and 2.0mA / cm 2 , the test voltage range for each cycle is 1.8V to 2.8V.
[0084] According to the test results, after the titanium dioxide nanolayer of Example 1 was sputtered on the diaphragm, the charge and discharge cycle performance of the battery was significantly improved. Specifically, as the number of cycles increased, the capacity of the battery remained stable, and after 100 cycles, the discharge voltage still remained at a high level.
[0085] Through the study of the mechanism of the diaphragm, it was found that Example 1 of the present invention uses a magnetron sputtering method to modify the diaphragm, and after depositing a titanium dioxide nanolayer on the diaphragm, the safety performance of the battery can be improved. This nanoscale metal oxide coating is used as a physical shield to allow lithium ions to pass through, while suppressing the shuttle effect of soluble polysulfides. At the same time, the amorphous metal oxide nanoscale coating prepared by magnetron sputtering technology has good structural uniformity and porosity, which increases the contact area between the electrolyte and the interlayer, so that the surface of the diaphragm has better wettability for the electrolyte, so that lithium can be evenly deposited on the negative electrode side, thereby realizing the uniform deposition process of lithium in space. Under the action of such a dual-functional coating, not only the shuttle effect of soluble polysulfides is solved, but also it is beneficial to the rapid conduction of lithium ions and promotes the dendrite-free growth of lithium, avoiding safety hazards such as internal short circuits in the battery.
[0086] Test Example 2:
[0087] The electrochemical performance test diagram of the lithium-sulfur full battery using the modified lithium-sulfur battery separator modified with titanium dioxide with different sputtering times in Example 1 is shown in FIG. Figure 1 , the test results are shown in Table 2.
[0088] Table 2 Effect of different sputtering times of titanium dioxide target on battery performance
[0089]
[0090] According to the test results, after the titanium dioxide nanolayer of Example 1 is sputtered on the separator, the charge and discharge cycle performance of the battery is significantly improved, which is specifically manifested in that as the number of cycles increases, the capacity of the battery remains stable, and after 150 cycles, the discharge voltage remains at a high level, while maintaining a high capacity retention rate, both above 50%. Among them, when the sputtering time is within the range of 4min to 20min, the first week charge and discharge coulomb efficiency is above 90%, which is higher than the polyethylene separator before modification.
[0091] Test Example 3:
[0092] The electrochemical performance test diagram of the lithium-sulfur full battery using the modified lithium-sulfur battery separator modified with indium oxide with different sputtering times in Example 2 is shown in FIG. Figure 2 , the test results are shown in Table 3.
[0093] Table 3 Effect of different sputtering times of indium oxide target on battery performance
[0094]
[0095] According to the test results, after the indium oxide nanolayer of Example 2 is sputtered on the diaphragm, the charge and discharge cycle performance of the battery is significantly improved, which is specifically manifested in that as the number of cycles increases, the capacity of the battery remains stable, and after 150 cycles, the discharge voltage remains at a high level, while maintaining a high capacity retention rate, both above 60%. Among them, when the sputtering time is within the range of 4min to 20min, the first week charge and discharge coulomb efficiency basically reaches more than 90%, which is higher than the polyethylene diaphragm before modification.
[0096] Test Example 4:
[0097] The electrochemical performance test diagram of the lithium-sulfur full battery using the modified lithium-sulfur battery separator modified with aluminum oxide with different sputtering times in Example 3 is shown in FIG. Figure 3 , the test results are shown in Table 4.
[0098] Table 4 Effect of different sputtering times of alumina target on battery performance
[0099]
[0100]
[0101] According to the test results, after the aluminum oxide nanolayer of Example 3 was sputtered on the diaphragm, the charge and discharge cycle performance of the battery was significantly improved. Specifically, as the number of cycles increased, the capacity of the battery remained stable, and after 150 cycles, the discharge voltage remained at a high level, while maintaining a high capacity retention rate, which was basically above 50%. Among them, when the sputtering time was in the range of 4min to 16min, the coulombic efficiency of charge and discharge in the first week was above 90%, which was higher than that of the polyethylene diaphragm before modification.
[0102] Test Example 5:
[0103] Table 5 Effect of modified lithium-sulfur battery separators modified with different metal oxides on battery performance
[0104]
[0105]
[0106] Note: The thickness of the metal oxide nanolayer in Example 5 ranges from 10 nm to 50 nm.
[0107] According to the test results, after the aluminum oxide nanolayer of Example 4 is sputtered on the diaphragm, the charge and discharge cycle performance of the battery is significantly improved, which is specifically manifested in that as the number of cycles increases, the capacity of the battery remains stable, and after 150 cycles, the discharge voltage remains at a high level, while maintaining a high capacity retention rate, all of which are above 50%. Among them, when the metal oxide is beryllium oxide, magnesium oxide, vanadium oxide, niobium oxide, titanium dioxide and indium oxide mixed in a mass ratio of 1:1, titanium dioxide and aluminum oxide mixed in a mass ratio of 1:1, and titanium dioxide and magnesium oxide mixed in a mass ratio of 1:1, the first cycle charge and discharge coulomb efficiency is above 82%; in particular, when titanium dioxide and indium oxide are mixed in a mass ratio of 1:1, titanium dioxide and aluminum oxide are mixed in a mass ratio of 1:1, and titanium dioxide and magnesium oxide are mixed in a mass ratio of 1:1, the first cycle charge and discharge coulomb efficiency is above 90%.
[0108] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A modified lithium-sulfur battery separator, characterized in that: The modified lithium-sulfur battery separator comprises a separator substrate and a metal oxide nanolayer, wherein the metal oxide nanolayer is uniformly deposited on the surface of the separator substrate by a physical vapor deposition method; The metal oxide is at least one of titanium dioxide, indium oxide, aluminum oxide, beryllium oxide, magnesium oxide, calcium oxide, barium oxide, zirconium dioxide, vanadium oxide, niobium oxide, chromium oxide, manganese oxide, technetium dioxide, rhenium heptoxide, silver oxide, zinc oxide, cadmium oxide, germanium dioxide, tin oxide, antimony trioxide, and bismuth oxide; The thickness of the metal oxide nanolayer is 10 nm to 50 nm.
2. The modified lithium-sulfur battery separator according to claim 1, characterized in that: The metal oxide is at least one of titanium dioxide, indium oxide and aluminum oxide.
3. The modified lithium-sulfur battery separator according to claim 1, characterized in that: The diaphragm substrate is any one of a polyethylene diaphragm, a polypropylene microporous diaphragm and a cellulose diaphragm.
4. A method for preparing the modified lithium-sulfur battery separator according to claim 1, characterized in that: The following steps are involved: A metal oxide nanolayer is uniformly deposited on the surface of a diaphragm substrate by a physical vapor deposition method to obtain a lithium-sulfur battery diaphragm modified with a metal oxide nanolayer.
5. The method for preparing the modified lithium-sulfur battery separator according to claim 4, characterized in that: The target material for depositing the metal oxide nanolayer is the corresponding metal oxide target material.
6. The method for preparing the modified lithium-sulfur battery separator according to claim 5, characterized in that: The process parameters for depositing the metal oxide nanolayer are: The background vacuum degree is 0.1×10 -5 Pa~9.9×10 -5 Pa, the working gas pressure is 0.25Pa~0.35Pa, and the purity of the metal oxide target is ≥99.99%; The target distance is 8cm to 12cm, the sputtering temperature is 20℃ to 30℃, and the sputtering time is 1min to 20min.
7. A lithium-sulfur battery, comprising a positive electrode, a separator, a negative electrode and an electrolyte solution; characterized in that: The diaphragm is the modified lithium-sulfur battery diaphragm according to claim 1; The positive electrode is obtained by grinding the sulfur-carbon composite material with Super-P carbon and polyvinylidene fluoride, dispersing the mixture in N-methylpyrrolidone, ball milling to obtain a positive electrode slurry, and coating the mixture on a metal substrate; The negative electrode is a polished lithium metal; The electrolyte solution is prepared by mixing 1,3-dioxolane and 1,2-dimethoxyethane in an equal volume ratio, adding lithium nitrate solution and lithium bis(trifluoromethanesulfonyl)imide, and mixing uniformly.
8. The lithium-sulfur battery according to claim 7, characterized in that: In the positive electrode, the sulfur-carbon composite material is obtained by heating sulfur and acetylene black at 140° C. to 150° C.; the mass ratio of the sulfur to the acetylene black is 7:3; and the metal substrate is aluminum foil or copper foil.
9. The lithium-sulfur battery according to claim 7, characterized in that: The mass ratio of sulfur-carbon composite material to Super-P carbon and polyvinylidene fluoride is 8:1:
1.
10. The lithium-sulfur battery according to claim 7, characterized in that: In the electrolyte solution, the mass fraction of lithium nitrate solution is 1.0%; the concentration of lithium bis(trifluoromethanesulfonyl)imide in the electrolyte solution is 1 mol / L.
Citation Information
Patent Citations
Independent functional interlayer for lithium-sulfur battery and preparation method thereof
CN109768284A
Composite positive pole piece, preparation method thereof and lithium-sulfur battery
CN116487532A
Diaphragm and preparation method thereof, battery and electric device
CN117525749A
Sulfur-carbon composite and method for manufacturing the same
KR1020150014793A
Separator for lithium sulfur batteries
US20200321582A1